2008
DOI: 10.1002/jor.20621
|View full text |Cite
|
Sign up to set email alerts
|

The human anterior cruciate ligament: Sex differences in ultrastructure and correlation with biomechanical properties

Abstract: The purpose of this study was to investigate the existence of sex-based differences in the ultrastructural characteristics of the human anterior cruciate ligament (ACL) as the underlying cause of differences in the structural and mechanical properties between sexes. The ACL of six male and six female cadaveric donors were randomly chosen from a pool of 10 male and 10 female ACLs that had previously been tested for their structural and mechanical properties. Eighteen tissue samples from the distal, proximal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 8 publications
1
59
0
2
Order By: Relevance
“…A female's smaller ACL size (Chandrashekar et al, 2005), lower ACL strength (Chandrashekar et al, 2006), and less-efficient ACL ultrastructure (Hashemi et al, 2008b) may collectively be a final disadvantage in leading to this injury. Indeed, additional study will be required to determine whether sex influences susceptibility to injury primarily by determining ACL size and strength or rather by affecting the likelihood that an injurious load will be applied.…”
Section: Implication To Sex-based Disparity In Acl Injury Ratesmentioning
confidence: 99%
“…A female's smaller ACL size (Chandrashekar et al, 2005), lower ACL strength (Chandrashekar et al, 2006), and less-efficient ACL ultrastructure (Hashemi et al, 2008b) may collectively be a final disadvantage in leading to this injury. Indeed, additional study will be required to determine whether sex influences susceptibility to injury primarily by determining ACL size and strength or rather by affecting the likelihood that an injurious load will be applied.…”
Section: Implication To Sex-based Disparity In Acl Injury Ratesmentioning
confidence: 99%
“…111 After adjusting for age and anthropometric factors, the female ACL has less collagen fiber density (area of collagen fibers/total area of the micrograph) 112 and decreased mechanical properties, including strain at failure, stress at failure, and modulus of elasticity. 113 Females are also reported to have greater lateral and medial posterior-inferior tibial slopes, 114,115 reduced coronal tibial slopes, 114 taller femoral notch heights, and smaller femoral notch widths than males.…”
Section: Anatomical and Structural Risk Factorsmentioning
confidence: 99%
“…Though our findings only revealed that the repeated application of incremental landing impact loads to intact male cadaveric specimens can induce ACL failure and tibiofemoral cartilage deformation and damage, we expect some differences in these outcomes for female specimens. Previous studies have shown that women displayed different ACL ultrastructure and biomechanical properties (Hashemi et al, 2008), and greater knee valgus during landing (Russell et al, 2006), compared to men; these differences are important risk factors for ACL failure. We therefore speculate that the application of our impact protocol to female cadaveric specimens in a physiological valgus position may potentially result in the occurrence of ACL failure at lower impact loads, and greater deformation and damage at lateral tibiofemoral cartilage compartments.…”
Section: Article In Pressmentioning
confidence: 97%